Both, toxin A and toxin B, are important in Clostridium difficile infection - Kuehne, Sarah A.; Cartman, Stephen T.; Minton, Nigel P. (Landes Bioscience, 2011)
The bacterium Clostridium difficile is the leading cause of healthcare associated diarrhoea in the developed world and thus presents a major financial burden. The main virulence factors of C. difficile are two large toxins, A and B. Over the years there has been some debate over the respective roles and importance of these two toxins. To address this, we recently constructed stable toxin mutants of C. difficile and found that they were virulent if either toxin A or toxin B was functional. This underlined the importance of each toxin and the necessity to consider both when developing countermeasures against Clostridium difficile infection (CDI). In this article we discuss our findings in the context of previous work and outline some of the challenges which face the field as a result.